The Impact of Supervisor Support, Empowerment, and Work Stress on Work Commitment and Engagement among Export-Import Staff - Suhardoyo Suhardoyo; A. Sudrajat; Roydawati Bunga Sihol; Awan Gumilang Hardandrito (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to determine the effect of supervisory support, empowerment, and work stress on work engagement through work commitment as a mediating variable. An empirical study was conducted on export-import staff employees at companies in KBN Cakung Jakarta using a questionnaire. The novelty of this research is that this is the first research to be conducted on export-import staff at KBN, and the results will be able to provide a positive impact on the company and society. This study is a descriptive study with a population of 143 staff employees at companies in KBN Cakung Jakarta. The sample selected was 100 employees obtained through cluster sampling, stratified sampling, and proportional random sampling techniques. The analysis method is path analysis processed with using structural equation modeling (SEM). The results of this study indicate that supervisor support coefficient value of 0,226 empowerment coefficient value of 0,570 effectively have a positive on work engagement directly. As well as a positive and direct effect between supervisor support coefficient value of 0,254 and the empowerment coefficient value of 0,428 on work commitment, while the work stress variable coefficient value of-0,569 has a negative and effect directly on work commitment and the work stress variable coefficient value of -0,440 has a negative and effect directly work engagement. The indirect effect of supervisor support coefficient value of 0,155 and empowerment coefficient value of 0,153 on work engagement variables through work commitment has a positive. As well as the indirect effect of work stress coefficient value of-0,145 on work engagement through work commitment has a negative. Based on the results of this study, it can be obtained that the variables of supervisory support, empowerment, and work stress have a direct significant effect on work commitment and have an impact on employee work engagement in the export-import staff section. And have an indirect impact on supervisory support and empowerment of Work Engagement through Work Commitment.